From walking artist… to walking visitor… to walking researcher - Castro, Laura (2018)
In this paper, we put forward a reading of the models of institutional relationship between art and the landscape, which has developed since the 1970s, along three lines: its creation, its reception, and its study, with the binding premise between the three being the act of walking, and those who walk. The reception of art and the place of the walking visitor is the theme, which has been most thoroughly developed, through an analysis of contemporary cases of exhibitions set in the landscape. The walking researcher arises inherently in any search for art situated in the landscape. The examination of the walking artist, understood in a free context here, stems from the institutionalisation of centres of art and landscape. Before looking into contemporary cases, it is worth taking a moment to consider the different types of relationship between the land and artistic practice, which define landscapes as either with, of or for art.